TORONTO CLINICAL NEUROPATHY SCORE AND MODIFIED TORONTO CLINICAL NEUROPATHY SCORE DIAGNOSTIC TESTS IN DISTAL DIABETIC SENSORIMOTOR POLYNEUROPATHY PATIENTS - Basuki, Mudjiani; Hamdan, Muhammad; Fadil, Fidiana,; Noormainiwati (International Journal of Psychosocial Rehabilitation, 2020)
Background: Distal diabetic sensorimotor polyneuropathy is a common complication that occurs in diabetes mellitus patients. Even though the number of diabetes mellitus patients has been increasing, the prevalence is still far from its actual numbers due to diagnostic and method criteria. Objectives: We aimed to determine Toronto Clinical Neuropathy (TCN) and modified Toronto Clinical Neuropathy (mTCN) scores in distal diabetic sensorimotor polyneuropathy patients. Methods: A cross-sectional study was carried out from October 29th, 2014, to June 1st, 2015, in 77 diabetes mellitus patients who visited an outpatient clinic. Polyneuropathy diagnosis was based on TCN and mTCN scores, with the gold standard of peroneal and/or sural nerve conduction velocity examination. Results: The area under curve value of the TCN score was 84.5% (95% CI: 74.7%-94.3%). A TCN diagnostic score above 4 had sensitivity, specificity, and accuracy of 96%, 40%, and 82%, respectively. On the other hand, TCN diagnostic scores above 8 had sensitivity, specificity, and accuracy of 72%, 80%, and 74%, respectively. The AUC value of the mTCN score was 81.9% (95% CI: 71.8%-92.1%). mTCN diagnostic score above 8 had sensitivity, specificity, and accuracy of 63%, 75%, and 66%, respectively. Conclusion: TNC scores above 4 could be used as a screening test, while scores above 8 could be used as a diagnostic test for distal DSP.